Family members' experience of seeking help for first‐episode psychosis on behalf of a loved one: a meta‐synthesis of qualitative research. Issue 3 (23rd June 2014) - Cairns, Victoria A.; Reid, Graeme S.; Murray, Craig
Abstract Aim Family members often play a vital role in seeking help for loved ones experiencing first‐episode psychosis. Understanding this experience is crucial in facilitating the help‐seeking process. Qualitative research offers valuable insight into the lived experience of family members who seek help on behalf of a loved one experiencing first‐episode psychosis. Method The current research presents a systematic review of qualitative studies exploring the family member experience of seeking help for first‐episode psychosis. Results A meta‐synthesis of 13 qualitative studies has revealed four themes relating to family members' experience of seeking help for first‐episode psychosis. These include a sense of not knowing, the reaching of crisis point, the impact upon the family member and the mediating role of interactions with others. A further synthesis of translation captures the interaction of these themes within this experience. Conclusions The findings provide a novel insight into this experience, suggesting implications for clinical practice. These include a focus upon the facilitation of early positive interactions with family members and for first‐episode psychosis to be presented to families in a normalizing manner. The need for future research that examines the experience of those who do not seek help from health services is discussed.